1994
DOI: 10.1007/bf00374574
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of prostaglandins in hypoxia-induced vasodilatation in isolated rabbit hearts. Relation to adenosine and KATP channels

Abstract: The mechanism of hypoxia-induced coronary vasodilation was studied in isolated, saline-perfused rabbit hearts under constant flow conditions. Reduction in the perfusion solution PO2 (from 520 +/- 6 to 103 +/- 9 mm Hg) under control conditions halved the coronary resistance and was accompanied by a significant release of the prostaglandin (PG) 6-keto-PGF1 alpha (from 1.8 +/- 0.3 to a maximum of 4.4 +/- 0.9 pmol min-1 g-1). The cyclooxygenase inhibitor, diclofenac (1 microM), blocked the release of PGI2 and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 34 publications
6
37
1
Order By: Relevance
“…Because prostacyclin is a hyperpolarizing vasodilator that acts via the adenylyl cyclase system (22,25,32) and enhanced prostacyclin release is a crucial mediator of hypoxic dilation of MCA of rats on normal salt diet (20), it is likely that a similar impairment of this pathway may contribute to loss of the vasodilator response to iloprost (and to reduced PO 2 ) that we observed in arteries of animals on a high-salt diet. In this respect, the present report provides the initial evidence that high-salt diet can also lead to an impaired coupling between membrane receptors and the ultimate electrophysiological response to reduced PO 2 in cerebral resistance arteries.…”
Section: Effect Of High-salt Diet On Electrical and Mechanical Responmentioning
confidence: 88%
“…Because prostacyclin is a hyperpolarizing vasodilator that acts via the adenylyl cyclase system (22,25,32) and enhanced prostacyclin release is a crucial mediator of hypoxic dilation of MCA of rats on normal salt diet (20), it is likely that a similar impairment of this pathway may contribute to loss of the vasodilator response to iloprost (and to reduced PO 2 ) that we observed in arteries of animals on a high-salt diet. In this respect, the present report provides the initial evidence that high-salt diet can also lead to an impaired coupling between membrane receptors and the ultimate electrophysiological response to reduced PO 2 in cerebral resistance arteries.…”
Section: Effect Of High-salt Diet On Electrical and Mechanical Responmentioning
confidence: 88%
“…Nakhostine and Lamontagne [29] showed that glibenclamide, a K + ATP channel antagonist, significantly attenuated hypoxia-and adenosine-induced vasodilation in isolated rabbit hearts. Kirsch et al [30] recently reported that adenosine activates an ATP-sensitive K + current in neonatal rat ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…inwardly rectifying K ϩ current; coronary vasodilation; protein kinase A; Kir2.1 CORONARY VASCULAR SMOOTH MUSCLE in guinea pig, rabbit, and rat hearts relaxes in response to acute hypoxia or a decrease in PO 2 (7,27,30,37). Vasodilation in response to hypoxia in coronary vascular smooth muscle is likely a protective response to increase blood flow to areas of low PO 2 .…”
mentioning
confidence: 99%